Use of a Nasal Cannula as a Preoxygenation Adjunct: A Randomized Crossover Study - Murphy Joel; Suvajit Podder; Savan Kumar Nagesh; Ramyatha Aithal; Aditya R. Devalla; Shaji Mathew (Anesthesiology Research and Practice)
Background. Preoxygenation prior to induction of general anesthesia is intended to increase the oxygen reserve in the lungs. This technique delays the onset of hypoxemia during the placement of the tracheal tube. Objective. To observe the benefits of oxygen through nasal cannula when used as an adjunct during preoxygenation. Methods. We enrolled 30 healthy volunteers and conducted a sequence of six preoxygenation tests. These included 3-minute tidal volume breathing and 8 vital capacity breaths, with and without oxygen flowing through the nasal cannula as an adjunct. Subjects were kept at a supine position with a face mask on their faces. Their baseline vitals were measured and end-tidal O2 (ETO2) was recorded at the end of each test. The comfort of each technique was also assessed. Results. When comparing the efficacy of the two preoxygenation methods, we found that the addition of oxygen through the nasal cannula improved the efficacy of preoxygenation with both the 3-minute tidal volume breathing method and the 8 vital capacity method (p<0.001). The three-minute tidal volume breathing technique had higher end-tidal oxygen when compared to the eight vital capacity breaths. Conclusions. The administration of oxygen through a nasal cannula during preoxygenation improves the efficacy of preoxygenation in healthy volunteers. Tidal volume breathing for three minutes achieves a higher end-tidal oxygen concentration compared to eight vital capacity breaths over one minute.